2012
DOI: 10.1101/gr.141887.112
|View full text |Cite
|
Sign up to set email alerts
|

Small noncoding differentially methylated copy-number variants, including lncRNA genes, cause a lethal lung developmental disorder

Abstract: An unanticipated and tremendous amount of the noncoding sequence of the human genome is transcribed. Long noncoding RNAs (lncRNAs) constitute a significant fraction of non-protein-coding transcripts; however, their functions remain enigmatic. We demonstrate that deletions of a small noncoding differentially methylated region at 16q24.1, including lncRNA genes, cause a lethal lung developmental disorder, alveolar capillary dysplasia with misalignment of pulmonary veins (ACD/MPV), with parent-of-origin effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
176
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(184 citation statements)
references
References 56 publications
(75 reference statements)
8
176
0
Order By: Relevance
“…In mice, replacing the lncRNA gene Fendrr with a reporter gene results in lung defects and perinatal death (84), a phenotype in agreement with clinical studies demonstrating that deletions within this locus in humans results in abnormal lung development and neonatal death (103). In contrast, a second study demonstrated that insertion of a premature transcriptional termination sequence within the same mouse locus results in prenatal death, body wall abnormalities, and heart malfunction (80).…”
Section: Animal Models and Lncrna Functionsupporting
confidence: 49%
“…In mice, replacing the lncRNA gene Fendrr with a reporter gene results in lung defects and perinatal death (84), a phenotype in agreement with clinical studies demonstrating that deletions within this locus in humans results in abnormal lung development and neonatal death (103). In contrast, a second study demonstrated that insertion of a premature transcriptional termination sequence within the same mouse locus results in prenatal death, body wall abnormalities, and heart malfunction (80).…”
Section: Animal Models and Lncrna Functionsupporting
confidence: 49%
“…Hundreds of lncRNAs are expressed in the lung, including lncRNAs that regulate developmental processes such as differentiation and proliferation in other contexts (Askarian-Amiri et al, 2011;Cabili et al, 2011; Kretz et al, 2012). Although there is no direct evidence indicating that lncRNAs regulate lung development, the deletion of a genomic locus containing lncRNAs upstream of Foxf1 is associated with lung developmental disorders normally associated with Foxf1 mutations, including pulmonary vascular defects (Szafranski et al, 2013). This suggests that these lncRNAs regulate Foxf1 activity during lung development and that they may be part of a larger group of lncRNAs influencing lung development as a whole.…”
mentioning
confidence: 95%
“…32 Similarly, we found that the highest positive correlation (0.77) for the lncRNA FENDRR was with a protein coding gene, FOXF1, transcribed bidirectionally on the opposite strand. 35 Additionally, the lncRNA HOTAIR, which resides in a HOXC gene cluster, is known to be co-expressed with HOXC genes, and overlaps HOXC11, displayed its highest positive correlation with multiple HOXC genes including HOXC11 (0.86), HOXC10 (0.72), HOXC13 (0.66), HOXC8 (0.44), and HOXC9 (0.38). 42 Next, we clustered the functional gene sets nominated by GSEA, which led to the identification of 3 main clusters (Fig.…”
Section: Prediction Of Onco-lncrna Functionmentioning
confidence: 99%
“…Additionally, even though our differential expression analysis only included tumors with matched normal tissue, the unpaired tumor samples appear to have expression levels similar to the paired tumor samples. Onco-lncRNA-21, also known as FENDRR, has been implicated in a lethal lung development disorder 35 and lung cancer. 34 As shown in Figure 3C, in addition to LUAD and LUSC, oncolncRNA-21 expression levels are also significantly downregulated in BLCA and CRC.…”
mentioning
confidence: 99%